2021
DOI: 10.15241/cdc.11.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Equity of Filipino Communities in COVID-19: A Framework for Practice and Advocacy

Abstract: The emergence and global spread of COVID-19 precipitated a massive public health crisis combined with multiple incidents of racial discrimination and violence toward Asian American and Pacific Islander (AAPI) communities. Although East Asian communities are more frequently targeted for instances of pandemic-related racial discrimination, multiple disparities converge upon Filipino communities that affect their access to mental health care in light of COVID-19. This article empowers professional counselors to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…The results of our study therefore supplement the existing body of research outlining the negative effects of racial discrimination on life satisfaction and mental health concerns among specific ethnic AAPI subgroups while contributing new information about the effects of COVID-19-related racial discrimination in Filipino Americans. Specifically, the findings from our study contribute to the emerging body of literature on COVID-19's impact among Filipino Americans (Chan & Litam, 2021;National Nurses United, 2020) and Filipinos (Montano & Acebes, 2020;Tee et al, 2020) by identifying the effects of pandemic-related discrimination on the Filipino American diaspora. Our findings suggest a pathway in which COVID-19related racial discrimination indirectly affects life satisfaction via increased depression and anxiety in Filipino Americans.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The results of our study therefore supplement the existing body of research outlining the negative effects of racial discrimination on life satisfaction and mental health concerns among specific ethnic AAPI subgroups while contributing new information about the effects of COVID-19-related racial discrimination in Filipino Americans. Specifically, the findings from our study contribute to the emerging body of literature on COVID-19's impact among Filipino Americans (Chan & Litam, 2021;National Nurses United, 2020) and Filipinos (Montano & Acebes, 2020;Tee et al, 2020) by identifying the effects of pandemic-related discrimination on the Filipino American diaspora. Our findings suggest a pathway in which COVID-19related racial discrimination indirectly affects life satisfaction via increased depression and anxiety in Filipino Americans.…”
Section: Discussionmentioning
confidence: 65%
“…Filipino American participants in the study may have found problem-focused disengagement coping more helpful for buffering the effects of racial discrimination on depression because they may have relied on traditional Indigenous coping responses that underscore virtues of patience, inner strength, flexibility, and hardiness (Sanchez & Gaw, 2007). For example, endorsing tiyaga and lakas ng loob represent culturally congruent strategies that may help Filipino Americans tolerate challenging or uncertain situations, such as instances of COVID-19-related racial discrimination (Chan & Litam, 2021). Finally, emotion-focused disengagement strategies include spending time alone, engaging in self-blame, and keeping thoughts and feelings to oneself (Addison et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from this study highlight the need for professional counselors to endorse an intersectional approach that considers the role of age and gender when counseling Chinese Americans facing COVID-19-related racial discrimination. Given that depression among Chinese Americans was associated with experiences of pandemic-related discrimination, counselors must be prepared to use culturally sensitive strategies to help Asian Americans raise their critical consciousness and use coping responses that mitigate the effects of race-based trauma and COVID-19-related discrimination (see Chan & Litam, 2021;Litam, 2020;Litam & Oh, 2020). Professional counselors can learn strategies to support Chinese Americans during the pandemic by consulting earlier literature (see Litam, 2020;Litam & Oh, 2020) and research on related topics.…”
Section: Clinical Implications For Counselorsmentioning
confidence: 99%